2018
DOI: 10.1111/1752-1688.12640
|View full text |Cite
|
Sign up to set email alerts
|

Observed Changes in Climate and Streamflow in the Upper Rio Grande Basin

Abstract: Observed streamflow and climate data are used to test the hypothesis that climate change is already affecting Rio Grande streamflow volume derived from snowmelt runoff in ways consistent with modelbased projections of 21st-Century streamflow. Annual and monthly changes in streamflow volume and surface climate variables on the Upper Rio Grande, near its headwaters in southern Colorado, are assessed for water years 1958-2015. Results indicate winter and spring season temperatures in the basin have increased sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 35 publications
2
57
1
Order By: Relevance
“…Trend analysis indicated increasing monthly mean streamflow during March ( p = 0.04, slope = 4.5 ft 3 /s/yr) and April ( p = 0.001, slope = 24.2 ft 3 /s/yr); no other months showed statistically significant trends, but the slopes of the time series regressions for June and July were strongly negative at −15.3 and −14.9 ft 3 /s/yr, respectively. These results indicate a shift in the timing of runoff toward earlier in the year, continuing a pattern observed in the URG (Chavarria and Gutzler 2018) and other southwestern U.S. basins (Robles et al 2017), and consistent with a previous analysis of snowmelt timing in Colorado (Clow 2010).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Trend analysis indicated increasing monthly mean streamflow during March ( p = 0.04, slope = 4.5 ft 3 /s/yr) and April ( p = 0.001, slope = 24.2 ft 3 /s/yr); no other months showed statistically significant trends, but the slopes of the time series regressions for June and July were strongly negative at −15.3 and −14.9 ft 3 /s/yr, respectively. These results indicate a shift in the timing of runoff toward earlier in the year, continuing a pattern observed in the URG (Chavarria and Gutzler 2018) and other southwestern U.S. basins (Robles et al 2017), and consistent with a previous analysis of snowmelt timing in Colorado (Clow 2010).…”
Section: Resultssupporting
confidence: 89%
“…These conditions, however, are not present in the RGHW. Previous studies have shown that SWE and SCA are changing in the URG due to changing climate (Chavarria and Gutzler 2018). This is illustrated by decreasing linear regression slopes for both SnowModel‐simulated basin peak SWE (−4.3 mm/yr, p < 0.01) and SnowModel‐simulated mean SCA during the melt period April–June (−0.005 SCA/yr or −0.5%/yr, p < 0.01) (Figure 5; Figure ; Sexstone 2020).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…1, middle column). On the Rio Grande, warming temperatures are contributing to reductions in the fraction of precipitation that becomes river flow (141,142).…”
Section: Water Resourcesmentioning
confidence: 99%